EVALUATING INTERPROFESSIONAL EDUCATION PRINCIPLE IN A LONGITUDINAL COMMUNITY-BASED PROGRAM FOR 3 SCHOOLS OF HEALTH PROFESSIONS: MEDICINE, NURSING, AND NUTRITION - Doni Widyandana (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Interprofessional education (IPE) is a method offered to support the collaboration of two health professions or more in order to create an ideal teamwork. This study aims to evaluate students’ interprofessional attitudes during the implementation of IPE in a community-based program among 3 health professions students.Method: Second and third year undergraduate students from three health profession schools in Faculty of Medicine, Universitas Gadjah Mada, medicine (n = 50), nursery (n = 50), and nutrition (n = 50), were recruited in 2015. Students were sent to a community setting in a small group of 10 consisting of those three schools’ students. They were assigned to a certain family and followed them longitudinally in a curriculum called the Community and Family Health Care program. Quantitative data were collected with a survey using Interprofessional Attitude Scale instrument containing 5 subscales (27 items): teamwork, roles and responsibilities; patient-centeredness; interprofessional biases; diversity and ethics; and community-centeredness. The items used 5-level Likert scale. Descriptive analysis was performed for the quantitative data and comparison among those three groups used Kruskal-Wallis test.Results: Most of the students strongly agreed they learned a lot about interprofessional attitudes during this program (mean scores of each subscale: 3.85, 4.19, 3.18, 3.83, and 3.99, respectively). There were significant differences among mean scores of each subscale (p< 0.05). Medical and nursery students had higher mean scores compared to nutrition students, except in the subscale of community-centeredness (p = 0.197).Conclusion: IPE can be implemented successfully in a longitudinal community-based education curriculum and benefits undergraduate students in studying interprofessional attitudes. The program should be evaluated and improved to assure all students to get equal benefits.